Resistance to pathologic cardiac hypertrophy and reduced expression of CaV1.2 in Trpc3-depleted mice - Han, Jung Woo (2016)
Sustained elevation of intracellular Ca2+ concentration ([Ca2+]i) reprograms cardiovascular cell fate, leading to cellular hypertrophy via Ca2+-calmodulin/calcineurin (Cn)/NFAT activation. Accumulating evidence suggests that transient receptor potential canonical (Trpc) channels play important roles in the development of pathologic cardiac hypertrophy. Here, we demonstrated that Trpc3 mediates pathologic cardiac hypertrophy in neurohumoral elevation via direct regulation of CaV1.2 expressions. Elevated PE (phenylephrine) was maintained in mice by continuous infusion using an osmotic pump. Wild-type (WT) mice, but not Trpc3−/− showed a sudden decrease in blood pressure (BP) or death following elevation of BP under conditions of elevated PE. Trpc3−/− mesenteric artery showed decreased PE-stimulated vasoconstriction. Analysis of morphology, function, and pathologic marker expression revealed that PE elevation caused pathologic cardiac hypertrophy in WT mice, which was prevented by deletion of Trpc3. Interestingly, protection by Trpc3 deletion seemed to be a result of reduced cardiac CaV1.2 expressions. Basal and PE induced increased expression of protein and mRNA of CaV1.2 was decreased in Trpc3−/− heart. Accordingly, altered expression of CaV1.2 was observed by knockdown or stimulation of Trpc3 in cardiomyocytes. These findings suggest that Trpc3 is a mediator of pathologic cardiac hypertrophy not only through mediating part of the Ca2+ influx, but also through control of CaV1.2 expressions.